Combining PD-L1 Expression and Standardized Uptake Values in FDG-PET/CT Can Predict Prognosis in Patients With Resectable Non–Small-Cell Lung Cancer. (11th August 2021) - Miyazawa, Tomoyuki; Otsubo, Kanji; Sakai, Hiroki; Kimura, Hiroyuki; Chosokabe, Motohiro; Morikawa, Kei; Furuya, Naoki; Marushima, Hideki; Kojima, Koji; Mineshita, Masamichi; Koike, Junki; Saji, Hisashi
Background: This study aimed to determine the relationship of programmed death-ligand 1 (PD-L1) expression and standardized uptake values in fluorodeoxyglucose–positron emission tomography/computed tomography (FDG-PET/CT) with prognosis in non–small-cell lung cancer (NSCLC). Methods: We retrospectively analyzed 328 NSCLC patients who underwent lobectomy/segmentectomy with lymph node dissection. PD-L1 expression was detected by immunohistochemically stained using the murine monoclonal antibody clone 22C3. The preoperative maximum standardized uptake value (SUVmax ) of FDG-PET/CT at the primary lesion; pathological factors including histological type, microscopic lymphatic, venous, and pleural invasion; and lymph node metastases in resected specimens was determined. Significant prognostic clinicopathologic factors were analyzed by univariate and multivariate analyses. Results: PD-L1 expression was higher in men, smokers, squamous cell carcinoma, advanced pathologic stages, positive venous invasion, positive pleural invasion, and high preoperative SUVmax (≥3). Postoperative survival analysis showed that both PD-L1 expression and preoperative SUVmax were significantly negative prognostic factors in univariate analysis for overall survival (OS) ( P = 0.0123 and P < 0.0001) and relapse-free survival (RFS) ( P = 0.0012 and P < 0.0001). Kaplan–Meier survival curves showed that the OS and RFS were the best in patients with negative PD-L1 expression and SUVmax < 3, intermediate in patients with positive PD-L1 expression and SUVmax < 3 and those with negative PD-L1 expression and SUVmax ≥ 3, and poor in patients with positive PD-L1 expression and SUVmax ≥ 3. Conclusion: Combining PD-L1 expression and preoperative FDG-PET/CT SUVmax in primary tumor might help in accurate prediction of postoperative prognosis in NSCLC patients.